Geokhod Propel Effort Mathematical Model; Applied Mechanics and Materials; Vol. 770 : Urgent Problems of Up-to-Date Mechanical Engineering - Blashchuk M. Yu. Mikhail Yurievich (Designing and Modelling of Machines and Mechanisms, 2015)
Title screen